Proceedings of the 35th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2002.994311
|View full text |Cite
|
Sign up to set email alerts
|

Implementing ERP systems in China

Abstract: This paper reports the findings of an exploratory study of R/3 users in China which was conducted in Spring 2000. The broad purpose of the study is to identify crucial implementation process and context variables which warrant closer attention in the study of IT-enabled organizational change. As companies display a great variety of ownership structures in China (including state-owned, foreign-invested, and privately-held firms), the role of ownership can be studied in relatively greater depth there than elsewh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 10 publications
1
36
1
Order By: Relevance
“…As such, Reimers (2002) points out that, Chinese managers may not trust the data provided and the suggestions made by ERP systems, and may even modify the (e.g. production and purchasing) quantities recommended by the system based on their own experiences.…”
Section: Trust Personal Common Sense/intuition Rather Than System Datmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, Reimers (2002) points out that, Chinese managers may not trust the data provided and the suggestions made by ERP systems, and may even modify the (e.g. production and purchasing) quantities recommended by the system based on their own experiences.…”
Section: Trust Personal Common Sense/intuition Rather Than System Datmentioning
confidence: 99%
“…This issue proves to have an impact on ERP adoption. For example, Reimers (2002) states that Chinese leaders may make centralised decisions on important IS issues without collecting and considering alternative ideas from a wider group of people. This issue was expected as an ERP exploitation barrier that could lead to inappropriate decisions regarding system functionality, analytical capabilities, use of these capabilities, general maintenance and system enhancement in Chinese firms.…”
Section: Cultural Barriersmentioning
confidence: 99%
“…• Reimers (2002Reimers ( , 2003a attempts to identify the crucial implementation process and context variables which warrant closer attention in the study of IT-enabled organizational change. The author focuses his study in a Chinese context.…”
Section: Implementation Success/failurementioning
confidence: 99%
“…As such, understanding context factors for ERP implementation is imperative because these factors might be unique to organizational culture or business processes that would significantly influence how ERP projects are carried out (Dezdar and Ainin, 2011;Kouki, Poulin and Pellerin, 2010). Recent empirical literature has thus witnessed increasing attention paid to unique local contexts such as China (Chien et al, 2007;Martinsons, 2004;Reimers, 2003), India (Poti and Kamalanabhan, 2009;Tarafdar and Roy, 2003) and the Middle East (Al-Turki, 2011;Amid, Moalagh and Zare Ravasan, 2012;Baki and Çakar, 2005). However, no empirical study has been found in the UAE context or based on contrasting theoretical frameworks.…”
Section: Introductionmentioning
confidence: 99%